Analysis of Compliance of Rural and Urban Land and Building Taxpayers in Pontianak - Widia Natakusuma Diah Pitaloka; Haryono; Rusliyawati Rusliyawati; Juanda Astarani (Poltanesa, 2025)
This study aims to examine the compliance level of Rural and Urban Land and Building Tax (PBB-P2) in Pontianak City, explore the challenges faced by the Regional Finance Agency (BKD) in its collection process, and assess the strategies implemented to enhance tax revenue. Employing a qualitative descriptive case study approach, the research collects data through interviews, analysis of PBB-P2 revenue realization documents, and literature review. The findings reveal that taxpayer compliance remains relatively low, primarily due to limited awareness, insufficient information dissemination, and administrative issues such as undelivered physical SPPT (Tax Due Notification Letters). To address these challenges, BKD Pontianak has adopted several strategies, including simplifying payment procedures, intensifying public outreach, and conducting direct appeals to residents. This underscores the practical need for improved education and accessible tax information to foster higher compliance rates. The findings also offer valuable insights for local governments in formulating more effective public engagement strategies, such as leveraging digital platforms and offering mobile tax services. Uniquely, this study contributes original value by presenting five years of consistent PBB-P2 compliance data—an area that has received limited academic attention—while also providing deeper qualitative insights into local-level tax collection issues and solutions.